The Implementation of Zero Reject Policy in Malaysia: A systematic Review - Ensimau, Nur Kamariah; Hamzah, Mohd Isa; Yasin, Mohd Hanafi Mohd; Nasri, Nurfaradilla Mohamad (Angstrom Centre of Education, 2022)
The Zero reject policy (ZRP) was policy introduced by Ministery of Education in Malaysia, December 2018 purposely to enhance the implementation of Education for All Policy in Malaysia. This systematic review was discuss to identify the factor that should be considerate in order to implement ZRP. The resercher used document analysis from previous research and the findings shown that, teacher knowledge, acceptance and readiness among the factor that influents the implementation of the ZRP in Malaysia.